The Effect of Using Context-Based Learning Videos on Global Warming Materials on Students' Problem-Solving Skills - Tamrin, Husni; Desnita, Desnita (Faculty of Science and Education, UIN Walisongo Semarang, 2023)
This study purpose was seen what there were effect of using context-based learning videos on global warming material on the problem solving students abilities of class XI at MAN 2 Pesisir Selatan. This research is a quasi-experimental research, posttest-only control design. The study population was all class XI IPA MAN 2 Pesisir Selatan who are registered in 2021/2022 school year. Sampling was conducted using cluster random sampling technique, selected class XI IPA 1 and XI IPA 3 as sampling. The data of this research is score of students' ability of problem solving. The research instrument was a written test in consist of 7 essay questions. Data analysis was carried out using the Normality Test, Homogeneity Test and U-test. The normality test, it was found that the experimental class was normally distributed while the control class was not normally distributed. The homogeneity test of the two sample classes shows that the two sample classes do not have a homogeneous variance. The results showed that the average problem-solving ability of the group for experimental was greater than the group for control. Using the U test (Man Withney) with a level of significance was 5%, the score of Zcount>Ztable is obtained. The results of the various problem solving abilities of each student could be identified. The average score of problem solving abilities in the experimental class was 90.48 while for the experimental class it was 76.06. This shows that the students' problem-solving abilities for the experimental class are higher than those for the control class. It can be concluded that there is an effect of using context-based learning videos on global warming material on the abilitiy of problem-solving in class XI students of MAN 2 Pesisir Selatan.